O capital científico nas crenças e atitudes de professores pedagogos em relação ao ensino de ciências - Gatto, Bibiana Abech (2021)
Scientific capital refers to a concept coined from the idea of cultural capital in Pierre Bourdieu. From it, it is possible to perceive how individuals relate to science and its contents, as well as the referring ways that these subjects give a kind of "consumption" of scientific content. In this sense, the present master's dissertation seeks to answer how scientific capital is evidenced from the beliefs and attitudes of pedagogical teachers in relation to science teaching? Therefore, the general objective built to direct the methodology of this investigation is to understand how this construction of scientific capital occurs. Therefore, its methodology was designed based on the idea of building an instrument of beliefs and attitudes related to the knowledge of recurrent themes in science classes from the 1st to the 5th year of elementary school, which also took into account the perception of the teachers - subjects of research - in relation to science education at this level of education. 22 pedagogical teachers participated in the investigation: 16 of them teaching in public (n = 4) and private schools (n = 18) and another 6 without acting in the classroom. After answering the instrument of beliefs and attitudes related to scientific capital, the pedagogues participated in focus groups where they could continue to express their concerns about the challenge of mediating science classes, without having a specific training. Being the nature of qualitative research and, therefore, being inserted in a phenomenological paradigm, not only the answers, but the teachers' speeches were used in the composition of categories that emerged throughout the research, and that allowed the researcher to propose an interpretive line during its analysis through Lawrence Bardin's Content Analysis. In the category “Interferences external and internal to the school in the practice of teachers in the Teaching of Natural Sciences”, we evaluated some situations external and internal to the school that may interfere in the disposition or motivation of teachers for Science Teaching. In another called "The view of the pedagogical teacher to Science", the interests and difficulties of the pedagogical teachers in teaching scientific concepts and contents in their Science classes in the Early Years of Elementary School were observed. Another category was referred to as “Science for the Teaching of Natural Sciences”; in it, it was verified how the practice of pedagogical teachers occurs in the daily teaching of Science. Finally, in the category "Influence of Scientific Capital in Science Education", it was about scientific capital, its collaboration and influence in the Science classes of the professors subject to the research. After the problematization of the constructed categories, it can be concluded that the need for universities and schools to offer more training in science to qualify the teaching and learning processes is unanimous among teachers. Therefore, this research has the potential to 9 stimulate basic and higher education institutions to reflect in order to provide opportunities for the construction and improvement of the scientific capital of pedagogical teachers, in order to close the existing gaps in science education in Brazil.